Cancer immunity - GÜLLÜOĞLU, ŞÜKRÜ (NOVA Science Publishers Inc., 2022)
Cancer is one of the leading causes of death worldwide. In the past, the effects of the immune system on cancer tumorigenesis and progression have been neglected since the immune system was conventionally believed to attack \"non-self\" cells only. Relatively recent findings have revealed that the immune system is constantly in search of neoplastic cells, and can recognize defects and threats by \"self\" cells as well. Both innate and adaptive immune cells are involved in various mechanisms that can detect and destroy cancer cells at any stage. However, tumor heterogeneity and subpopulation evolution in tumors make cancer find ways to escape immune pressure and even use immune cells in its favor. This chapter is about how the immune system is involved in the tumorigenesis and progression of cancer, from tumor recognition and development of the first response, inflammation and the tumor microenvironment, immune surveillance, and immune editing, and to immune escape.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; İmmünoloji; Diğer; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Tıbbi Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Microbiology and Clinical Microbiology; Immunology; Other; Internal Medicine Sciences; Internal Diseases; Oncology; Medical Genetics; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Moleküler Biyoloji ve Genetik; Mikrobiyoloji; ONKOLOJİ; TIP, GENEL & DAHİLİ; İMMÜNOLOJİ; MİKROBİYOLOJİ; GENETİK VE KALITIM; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; ONCOLOGY; MEDICINE, GENERAL & INTERNAL; GENETICS & HEREDITY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Mikrobiyoloji (tıbbi); Dahiliye; Genetik (klinik); Aile Sağlığı; Tıp (çeşitli); Genel Tıp; İmmünoloji ve Mikrobiyoloji (çeşitli); Genetik; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Microbiology (medical); Internal Medicine; Genetics (clinical); Family Practice; Medicine (miscellaneous); General Medicine; Microbiology; Immunology and Microbiology (miscellaneous); Genetics; Life Sciences